"THE WAR FOR THE FARE": HOW DRIVER COMPENSATION AFFECTS BUS SYSTEM PERFORMANCE. (18th March 2015) - Johnson, Ryan M.; Reiley, David H.; Muñoz, Juan Carlos
<x xml:space="preserve">Abstract</x> Prior to 2007, two systems of bus driver compensation coexisted in Santiago, Chile: one paid drivers per passenger transported, while the other paid a fixed wage. Per‐passenger drivers engaged in "The War for the Fare, " altering their driving patterns to compete for passengers. Examining these systems on similar routes in Santiago, we observed two key findings. Compared with the fixed‐wage system, the per‐passenger system leads to (1) 13% shorter passenger wait times, via reduced bunching of buses and (2) 67% more accidents per kilometer driven, via more aggressive driving. We discuss implications for the design of incentives in public transit. (JEL L92, M52, R41)